Chemistry, Analysis, Pharmacokinetics and Pharmacodynamics Aspects of Lorcaserin, a Selective Serotonin 5-HT2C Receptor Agonist: An Update - Sharma, Sanjay; Aware, Komal S.; Hatware, Ketan; Patil, Kiran (Mini Reviews in Medicinal Chemistry, 2020)
This review refers to the all-inclusive details of Lorcaserin Hydrochloride on comprehensive information about the synthesis, analytical methods, pharmacodynamics, pharmacokinetics, drug interactions and adverse effects. Lorcaserin Hydrochloride is chemically (R)-8-Chloro-1-methyl-2,3,4,5- tetrahydro-1H-3-benzazepine hydrochloride. Lorcaserin HCl is a novel, synthetic, centrally-acting selective serotonin C (5-HT2c) receptor, l agonist, which results in increased satiety and decreased food consumption in patients. Headache, dizziness and nausea are the most common side effects associated with this drug. Lorcaserin HCl has two major metabolites, one conjugated with glucuronide called N-carbamoyl glucuronide which is excreted in urine and the second Lorcaserin N-sulfamate, which is circulated in the blood. Lorcaserin HCl is synthesized using four different schemes of which a six-step method that resulted in 92.3% yield with 99.8% of purity is employed for scale-up production. It is analyzed quantitatively in the plasma and brain tissue matrix of rats by Ultra Performance Liquid chromatographic (UPLC) method using MS-MS (Mass Spectrometric) detection.
Keywords: appetite suppressant